Research on instrument mix and regional suitability of digital publishing industrial policies: An empirical exploration based on qualitative comparative analysis of fuzzy set - Sirui Li; Johnny Fat Iam Lam (PLoS ONE, 2026)
Taking the digital publishing industry as its research object and employs the fuzzy-set qualitative comparative analysis (fsQCA) method to systematically examine the causal relationships among the Instrument Mix, regional conditions, and industrial performance, drawing on policy texts and development data from 16 major Chinese provinces. The findings indicate that neither a single Policy instrument nor an isolated regional condition is sufficient to sustain high-quality development; rather, industry success depends on specific configurations of multiple interacting conditions. Content application and scenario promotion, together with industry chain shaping and cluster development, form the core elements of multiple high-performance pathways. In contrast, fiscal and financial instruments play a relatively peripheral role, confirming both synergistic and substitutive relationships among Policy instruments. Further path analysis reveals three distinct realization logic in the digital publishing industry: (1) a regional environment–driven model relying on economic and cultural endowments; (2) a policy–economy dual-drive model characterized by joint government–market action; and (3) a systemic synergy model where multiple factors interact comprehensively. In contrast, non-high-performing configurations demonstrate causal asymmetry, indicating that industrial underperformance is not a simple inversion of success but rather the result of compensatory interactions among regional conditions.